(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The present study was conducted during November 2014 to June, 2015 with biorational approaches for combating tomato borer, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) using Vertimec 1.8EC (Abamectin), Tracer 45SC (Spinosad), mechanical control (hand picking), 3 Neem products and an untreated control following Randomized Complete Block Design with 3 replications. The lowest level of fruit borer infestation (11.05% by number) at entire fruiting seasons and at early (11.05%), mid (10.88%) and late (11.28%) fruiting season was obtained from Tracer 45EC treated plot. The highest marketable yield (46.00 t/ha) was produced in the plot treated with Tracer 45SC sprayed @ 0.4 ml/L of water at 15 days interval. The marketable yield in plots treated with Vertimec 1.8EC @ 1.2 ml/L of water at 15 days interval was 37.67 t/ha and the plot sprayed with neem seed kernel extract @ 50 g/L of water at 15 days interval yielded 36.17 t/ha. The highest benefit cost ratio of 6.84 was obtained from the plot applied with Tracer 45SC followed by 6.39 obtained in the plots using Vertimec 1.8EC and this was followed by 6.18 found in neem seed kernel extract treated plot. Tracer 45SC was the most effective against tomato fruit borer. Bangladesh J. Agril. Res. 45(1): 11-20, March 2020